Understanding the Impact of Privacy Calculus on Social Media Self-disclosure: A Conceptual Framework and Research Proposition - Zhu, Luhui; Omar, Bahiyah (Jogjakarta Communication Conference (JCC), 2023)
Most social media platforms are encouraging users to disclose as much as possible due to self-disclosure on social media being the key value to the success of these platforms. Yet, when privacy breaches grow more and more frequent, individuals tend to do privacy calculations before self-disclosure. There are many factors that impact user self-disclosure behavior. On the basis of the privacy calculus theory, we developed a conceptual model to investigate the impact of perceived benefits and perceived risks on social media self-disclosure and proposed related research propositions, with the aim of revealing the impact mechanism of privacy calculus on social media self-disclosure and examining the effects of trust in platform, information sensitivity, privacy settings, and government regulation on user privacy calculus. Theoretically, the contribution of this study is the development of a privacy calculus model that reveals the user's privacy decision-making process. In terms of practical significance, this study may assist social media providers in better understanding users' privacy choices, decreasing privacy concerns, and enhancing user self-disclosure.